PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN DENGAN STRATEGI BISNIS SEBAGAI MODERASI (Studi Empiris Perusahaan Manufaktur Sektor Makanan Dan Minuman Yang Terdaftar Di BEI Tahun 2019 – 2021) - Stefania Lewa Lam; Antoni Antoni (Jurnal Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of intellectual capital on financial performance with a business strategy as moderator. The population used in this study are food and beverage manufacturing companies listed on the Indonesia Stock Exchange for the 2019- 2021 period. The sampling technique used in this study was purposive sampling based on the criteria, in order to obtain 16 samples of companies in the food and beverage sector that met the criteria.This study used SPSS 21 tools. Moderation regression analysis was used in this study. Based on the results of data analysis using the t test, it is known that intellectual capital does not have a significant direct effect on financial performance, but business strategy can moderate the effect of intellectual capital on financial performance. Thus, companies must recognize intellectual resources and develop business strategies that take into account their needs.